An Exemination Of The Effects Of Service Quality And Satisfaction On Customers Behavior Intentions In E-Shoping: An Empirical Study With Comparision Of Taiwan And Vietnam - Tran, Van-Dat; Nguyen, Minh Dung; Linh Vo, Thi Ngoc; Dinh, Thu Quynh (Bright Publisher, 2021)
The purpose of this paper to examine the relationship among e-service quality and e-satisfaction and behavioral intention, to reveal any difference across Taiwan and Vietnam. Data from a survey of 891 online consumers, 409 respondents in Taiwan and 482 respondents in Vietnam were used to test the research model. Confirmatory factor analysis was conducted to examine the reliability and validity of the measurement model, and the structural equation modeling technique was used to test the research model. Data analysis involved the comparison of two models using structural equations modeling. The prevailed model reveals that e-service quality has a positive effect on e-satisfaction in both Taiwan and Vietnam, explored the influence of customer e-satisfaction on behavioral intention in Vietnam and Taiwan. E-service quality played a stronger positive role for online shoppers in Taiwan as compared to their counterparts in Vietnam. Such differences in determinants of customer satisfaction may due to the market contexts in different parts of the world.